Influences of Traditional Mulches on Flower Production and Petal Coloration of Dianthus (Dianthus Chinensis Lin.) - Kabir, MH; Solaiman, AHM; Das, N; Uddin, AFMJ (Progressive Agriculture, 2013)
An experiment was conducted to understand the effect of traditional mulches on plant growth, flower induction, petal coloration and yield of Dianthus chinensis at Horticultural Farm, Sher-e-Bangla Agricultural University, Dhaka. Four mulch treatments C, control; SM, straw mulch; WHM, water hyacinth mulch; BPM, black plastic mulch were examined under this study. Black plastic mulch showed better performance than other treatments. Highest plant and flower growth, early flowering and maximum number of flowers were observed from black plastic mulch treatment followed by water hyacinth mulch and straw mulch respectively whereas the lowest was observed from control. Deep colored flower was produced from black plastic mulch treated plants and light colored flower from control. DOI: http://dx.doi.org/10.3329/pa.v18i2.17462 Progress. Agric. 18(2): 35 - 40, 2007